(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Each year, tons of weeds are burned or allowed to dry throughout the world. Despite folklore claims that Commelina benghalensis can treat leprosy, fever, snake bites, jaundice, sore throats, headaches, and constipation in both humans and animals, the ubiquitous Indian plant always dies the same way every year. By creating a formulation based on the evaluation of its potential ethnomedicinal properties, the current work attempts to utilize this weed. Using solvents with increasing polarity, the complete plant was extracted once at a time. The anti-ulcer and laxative efficacy of each extract was investigated using appropriate animal models. The ethnomedicinal claims of the plant were supported by the discovery that the methanolic extract was the most bioactive, followed by the aqueous extract. Important classes of phytoconstituents such phenolics, alkaloids, saponins, steroids & triterpenoids, flavonoids, and carbohydrates were found by phytochemical screening. From the purified fraction of the most bioactive extract, many chemicals, including stigmasterol and β-sitosterol, were discovered using GC-MS. Using TLC experiments and HPTLC, a chromatographic fingerprint was created. Effervescent granules of the methanolic extract were created and tested on animal models in order to bring the research to the public for their benefit. They were found to be effective as an anti-ulcer and laxative, which was compatible with our goal to create a "Best from Waste" product.